Recent developments in photovoltaic-thermoelectric combined system - D. Raut, Piyush; V. Shukla, Vishal; S.Joshi, Sandeep (International Journal of Engineering and Technology, 2018)
The photovoltaic system converts solar radiation into electricity. The output of the solar photovoltaic systems is strongly depending on the operating cell temperature. The power output of photovoltaic system reduces as the operating cell temperature increases. Several techniques have been reported in the literature to maintain the low operating temperature of the solar cell by utilizing module heat for separate thermal application. Integration of photovoltaic thermoelectric (PV-TE) system is one of these techniques. In these PV-TE systems, the hot junctions of thermoelectric modules are coupled with the photovoltaic. The thermoelectric module uses heat from PV system and generates additional power. This PV-TE system not only generates more power but also improves the PV efficiency. The present article reports a comprehensive review of latest developments in the PV-TE systems. A detailed classification, key outcomes of published research and the future research scope are discussed in this article.Â Â
Keywords: Photovoltaic; Thermoelectric; Indirect; Direct; BIPV.